2015
DOI: 10.1039/c5cy00253b
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of preparation method for Pd doped Cu/Al2O3 catalysts for selective acetylene hydrogenation

Abstract: Pd doped Cu catalysts have been prepared by co-impregnation, sequential impregnation and a colloidal approach. In each case, the Cu : Pd ratio was optimised leading to catalyst activity which exceeded that offered by monometallic Cu at low temperature (393 K and below) but with a product selectivity which suggests the reaction is still taking place on a Cu surface (i.e., high ethylene selectivity). Pd is therefore thought to influence hydrogen dissociation rates and enhance spillover onto Cu sites. Catalytic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 54 publications
0
55
0
Order By: Relevance
“…Of course, the true industrial process differs from catalyst testing in this work since the feed stream contains a large excess of ethylene. This additional complexity was not accessed here but has been reported elsewhere [22]. 75:1 and 100:1 CuPd/Al 2 O 3 catalysts also show a considerable increase in activity following treatment in CO, although differ in product selectivity from other samples.…”
Section: Impact Of Segregation Of Catalyst Activity and Selectivitymentioning
confidence: 77%
See 2 more Smart Citations
“…Of course, the true industrial process differs from catalyst testing in this work since the feed stream contains a large excess of ethylene. This additional complexity was not accessed here but has been reported elsewhere [22]. 75:1 and 100:1 CuPd/Al 2 O 3 catalysts also show a considerable increase in activity following treatment in CO, although differ in product selectivity from other samples.…”
Section: Impact Of Segregation Of Catalyst Activity and Selectivitymentioning
confidence: 77%
“…Several other monometallic [38][39][40], bimetallic [41][42][43][44], trimetallic [45] and metal-free catalysts [46,47] have been shown to offer high alkene selectivity, although they typically require activation and/or use at elevated temperatures. This is in contrast to CuPd catalysts which can be activated and used at much more moderate temperatures [21,22]. These catalysts differ from industrial catalysts in that Pd is not thought to be the active site, but acts as a site for hydrogen dissociation with the reaction taking place on a Cu surface.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Based on density functional theory calculations reported by Fu and Luo [63] it appears that Pd clusters which encompass both the surface and near surface layers represent sites where hydrogen dissociation should be more favourable than on monometallic Cu indicating that it may not be necessary to form single atom sites in the alloy before enhanced activity is observed. McCue et al have more recently explored different preparation methods for CuPd catalysts and found that any preparation route which enhances activity results in decreased ethylene selectivity and as such a balance between activity/selectivity must be reached [64]. Testing of the most selective catalyst (50 : 1, Cu : Pd atomic ratio prepared by sequential impregnation) under more industrially relevant conditions demonstrated that good ethylene selectivity can be achieved under competitive conditions, although ethane selectivity increases when operated at higher pressure [64].…”
Section: Use Of Pd To Enhance Activity Of Other Metalsmentioning
confidence: 98%
“…McCue et al have more recently explored different preparation methods for CuPd catalysts and found that any preparation route which enhances activity results in decreased ethylene selectivity and as such a balance between activity/selectivity must be reached [64]. Testing of the most selective catalyst (50 : 1, Cu : Pd atomic ratio prepared by sequential impregnation) under more industrially relevant conditions demonstrated that good ethylene selectivity can be achieved under competitive conditions, although ethane selectivity increases when operated at higher pressure [64]. Therefore whilst CuPd catalysts can operate at industrially relevant temperatures it is unlikely that they could be used at the pressures used within current industrial reactors which may limit potential application.…”
Section: Use Of Pd To Enhance Activity Of Other Metalsmentioning
confidence: 98%